2019
DOI: 10.21851/obr.43.01.201903.83
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory muscle tenderness in burning mouth syndrome: A case control study

Abstract: The aim of this study is to evaluate the masticatory muscle tenderness in burning mouth syndrome (BMS) patients. A total of 102 patients (48 with BMS and 54 with non-BMS) that attended the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Corsalini et al [7] reported that 72.7% of patients with BMS showed oral parafunctional habits, and 50% of patients showed tenderness on palpation of the masticatory muscles; there was a statistically significant association between temporomandibular disorders (TMDs) and BMS. Yoon and Ryu [8] reported that around 85.4% of patients with BMS showed tenderness on masticatory muscle palpation. Takahashi et al [9] reported that pushing or placing the tongue on the lower teeth may increase masticatory muscle activity in a study using electromyography.…”
Section: Several Studies Have Reported An Association Betweenmentioning
confidence: 99%
“…Corsalini et al [7] reported that 72.7% of patients with BMS showed oral parafunctional habits, and 50% of patients showed tenderness on palpation of the masticatory muscles; there was a statistically significant association between temporomandibular disorders (TMDs) and BMS. Yoon and Ryu [8] reported that around 85.4% of patients with BMS showed tenderness on masticatory muscle palpation. Takahashi et al [9] reported that pushing or placing the tongue on the lower teeth may increase masticatory muscle activity in a study using electromyography.…”
Section: Several Studies Have Reported An Association Betweenmentioning
confidence: 99%